PRAKTIK ADAT PERNIKAHAN SALEP TARJHE MASYARAKAT MADURA DI KELURAHAN BATU LAYANG KECAMATAN PONTIANAK UTARA KOTA PONTIANAK PERSPEKTIF HUKUM ISLAM - Amal, Amal; Marluwi, Marluwi; Wibowo, Arif (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
This study aims to uncover and clarify the actual practice of the customary marriage known as salep tarjhe, including the underlying philosophy and reasons for its prohibition, as well as its perspective from Islamic law within the Madurese community of Batu Layang. The research employs two main analytical frameworks: symbolic interactionist theory and Islamic law concerning marital issues. Using a sociological approach, this field research is supported by a literature review, with the author collecting primary data directly through interviews and documentation. The informants for this study include the couples involved, their parents, religious leaders, traditional elders, and the local community. The findings indicate that religious and community leaders in Batu Layang widely permit salep tarjhe marriages, asserting that they do not contradict Islamic sharia. The prohibition is found to stem from myths passed down through generations, such as beliefs that the marriage could lead to financial hardship, divorce, or infertility. This myth is classified as ‘urf fasid (corrupt custom) because it is inconsistent with Islamic principles. Conversely, some members of the general public still forbid this practice due to their belief in these myths. From an Islamic legal standpoint, the salep tarjhe marriage is deemed permissible (mubah) as there is no specific prohibition mentioned in the Quran, Hadith, or the views of codified fiqh scholars.